2003
DOI: 10.4319/lo.2003.48.5.1732
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition of single cells of various strains of marine Prochlorococcus and Synechococcus using X‐ray microanalysis

Abstract: We measured the elemental composition of single cells from six strains of marine Prochlorococcus and two strains of marine Synechococcus by X-ray microanalysis in the transmission electron microscope (TEM), which allows measurements of all major elements in cells without any fixation or staining. . Elemental composition varied widely in relation to strains and growth media. However, C : P and N : P ratios were above the Redfield ratio in all Prochlorococcus strains and one of the Synechococcus strains (WH 8103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
149
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(173 citation statements)
references
References 44 publications
(65 reference statements)
20
149
4
Order By: Relevance
“…Using the flowcytometer we could not detect these changes. The findings on the variations in N and P quota are in agreement with the observations that the cellular composition of pico-phytoplankton is subject to substantial change, for instance due to changes in the physico-chemical environment (Bertilsson et al, 2003;Heldal et al, 2003;Veldhuis et al, 2005). However, the absolute values that we report were higher than reported in other studies.…”
Section: àsupporting
confidence: 93%
See 2 more Smart Citations
“…Using the flowcytometer we could not detect these changes. The findings on the variations in N and P quota are in agreement with the observations that the cellular composition of pico-phytoplankton is subject to substantial change, for instance due to changes in the physico-chemical environment (Bertilsson et al, 2003;Heldal et al, 2003;Veldhuis et al, 2005). However, the absolute values that we report were higher than reported in other studies.…”
Section: àsupporting
confidence: 93%
“…The N and P quota in Synechococcus ranged from 1.4-1.5 Â 10 À15 mol N cell À1 and 0.06-0.11 Â 10 À15 mol P cell À1 under nutrient-replete conditions to 1.5-2.9 Â 10 À15 mol N cell À1 and 0.02-0.03 Â 10 À15 mol P cell À1 under P-limited conditions (Table 3). Similarly low N and P quota were measured in two strains of Synechococcus (Heldal et al, 2003) (Table 3). These values are typically one to two orders of magnitude lower than those reported in our study.…”
Section: àsupporting
confidence: 57%
See 1 more Smart Citation
“…Relatively small differences in nutrient utilization or regional adaptation in cyanobacteria translates into biochemical responses that are reflected in variations in elemental composition of the cells. P quotas for marine cyanobacteria have been reported to vary over approximately an order of magnitude (e.g., 22-116 amol/cell; Heldal et al, 2003;Twining et al, 2010), consistent with the suggestion that cyanobacteria possess radical surface modification mechanisms to cope with nutrient limitation, such as replacement of surface phospholipids with sulfolipids (Van Mooy et al, 2006). In our study, we observed a decreased role for protein in cell surface reactivity, and increased role for carbohydrates and lipids, as media N:P ratios departed from the reference condition of 14.5.…”
Section: .Discussionmentioning
confidence: 99%
“…In the Sargasso Sea, Prochlorococcus cell numbers peak during the summer at depths between 80 and 200 m, whereas Synechococcus cells reach their maximum density during spring blooms in surface waters. Synechococcus cells are slightly larger (0.62-1.56 mm 3 compared to 0.077-0.22 mm 3 for Prochlorococcus (Heldal et al, 2003)), and thus account for a higher proportion of primary producer biomass than cell numbers would suggest.…”
Section: Introductionmentioning
confidence: 91%